(untitled) (Medico Legal Update, 2021)
The aim of the research is to find out the effect of the (face-conclude-answer) strategy on the achievement of fourth-grade students in chemistry and branched thinking. Research sample was 53 students divided into two groups: A group was 27 students as experimental group and B group was 26 students as control then equalized in the following variables: academic achievement of the chemistry subject for the third intermediate grade, previous scientific knowledge of their information, intelligence test, chronological age and branched thinking test. The test was 35 items, where 26 was multiple choices question and 9 are article paragraphs. The validity was verified after the experiment in the academic year 2019-2020 by the researcher on the two research groups and according to the teaching plans that were prepared for them and applied the achievement test and the results showed the superiority of the experimental group that was studied according to the strategy (faced -conclude- answer) on the group that studied according to the usual method in a variable Academic achievement.